2012
DOI: 10.1007/s00402-012-1534-3
|View full text |Cite
|
Sign up to set email alerts
|

Bridging knee arthrodesis for limb salvage using an intramedullary cemented nail: a retrospective outcome analysis of a case series

Abstract: Bridging knee arthrodesis with an intramedullary nail is a valuable salvage procedure with acceptable clinical results. As recurring infection remains the most challenging complication, regular clinical and radiological follow-up examinations are necessary following implant-related knee arthrodesis to allow timely intervention in case of loosening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 32 publications
1
10
0
1
Order By: Relevance
“…They found that the average operative time for the procedure lasted 141 minutes and the mean estimated blood loss was 753 mL, which was comparable to revision TKA. Over a mean follow-up period of 56.4 months, a 30% complication rate was noted (range of 11.4%-81.8% from past studies) (Table 1) and a 90% (9 of 10 patients) survivorship of the arthrodesis was recorded with no evidence of residual infection or prosthesis failure [12,22,28,29,33] . One out of the ten patients experienced a recurrent infection which fell in the range of persistent or recurrent infection rates (0-45.5%) seen in past studies [12,13,20,22,28,33] (Table 1).…”
Section: Combination Of Different External Fixationmentioning
confidence: 96%
See 3 more Smart Citations
“…They found that the average operative time for the procedure lasted 141 minutes and the mean estimated blood loss was 753 mL, which was comparable to revision TKA. Over a mean follow-up period of 56.4 months, a 30% complication rate was noted (range of 11.4%-81.8% from past studies) (Table 1) and a 90% (9 of 10 patients) survivorship of the arthrodesis was recorded with no evidence of residual infection or prosthesis failure [12,22,28,29,33] . One out of the ten patients experienced a recurrent infection which fell in the range of persistent or recurrent infection rates (0-45.5%) seen in past studies [12,13,20,22,28,33] (Table 1).…”
Section: Combination Of Different External Fixationmentioning
confidence: 96%
“…They noted an average leg length discrepancy of 15 mm (+/-15 mm), 3 recurrent cases of infection, and 2 minor complications. The average SF-36 score for physical function was 21.8, an inferior score when compared to other arthrodesis procedures as well as TKA and transfemoral amputation [22] . Bartlett et al retrospectively analyzed 10 patients who underwent a custom-made cemented Stanmore (Stanmore Implants Worldwide, Middlesex, UK) arthrodesis procedure, 9 of 10 having undergone previous yet unsuccessful attempts to eradicate their knee infection.…”
Section: Combination Of Different External Fixationmentioning
confidence: 99%
See 2 more Smart Citations
“…Different techniques for knee arthrodesis have been reported, including plate and screw osteosynthesis, external fixation and intramedullary nailing, the latter two being the most often preferred in the presence of bone infection [10,12,13,15,[18][19][20][21]. Whereas the proposed techniques do achieve bone fusion and infection control in the majority of cases, residual limb-length discrepancy and possible nonunion are the primary limits of knee arthrodesis following septic TKA.…”
Section: Introductionmentioning
confidence: 99%